Produk Pembiayaan Modal Usaha Terhadap Peningkatan Kinerja Bank Pembiayaan Rakyat Syariah Hasanah Pekanbaru - Rahmawati, Indah (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is motivated by the financing carried out by PT BPRS Hasanah which has increased every year, however, seeing the condition of the bank's performance which has decreased as seen from its Return On Assets, namely the bank's ability to optimize the use of assets to obtain optimal profits. This research aims to determine the effect of business capital financing on improving bank performance. In conducting this research the author used a mixed methods method, namely a combination of quantitative and qualitative methods in one research, where one method is more dominant over the other method. Less dominant methods are only positioned as complementary methods for additional data. Data collection techniques use observation, interviews and questionnaires. In analyzing the data the author used the results of the questionnaire and finally through analysis of each variable. The results of this research are that the financing carried out by PT BPRS Hasanah Pekanbaru has gone well and the performance of BPRS Hasanah has been categorized as healthy and the results of the analysis show that there is a positive relationship between business capital financing which has a significant effect on increasing the performance of BPRS Hasanah.